Perioperative Outcome of Robotic Approach Versus Manual Videothoracoscopic Major Resection in Patients Affected by Early Lung Cancer: Results of a Randomized Multicentric Study (ROMAN Study) - Veronesi, Giulia; Abbas, Abbas El-Sayed; Muriana, Piergiorgio; Lembo, Rosalba; Bottoni, Edoardo; Perroni, Gianluca; Testori, Alberto; Dieci, Elisa; Bakhos, Charles T.; Car, Shamus; Luzzi, Luca; Alloisio, Marco; et al. (Frontiers in Oncology, 2021)
Introduction: We report the results of the first prospective international randomized control trial to compare perioperative outcome and surgical radicality of the robotic approach with those of traditional video assisted surgery in the treatment of early-stage lung cancer. Methods: Patients with clinical stage T1-T2, N0-N1 non small cell lung cancer (NSCLC) were randomly assigned to robotic resection or video-assisted thoracic surgery (VATS) resection arms. The primary objective was the incidence of adverse events including complications and conversion to thoracotomy. Secondary objectives included extent of lymph node (LN) dissection and other indicators. Results: This trial was closed at 83 cases as the probability of concluding in favor of the robot arm for the primary outcome was null according to the observed trend. In this study, we report the results of the analysis conducted on the patients enrolled until trial suspension. Thirty-nine cases were randomized in the VATS arm and 38 in the robotic arm. Six patients were excluded from analysis. Despite finding no difference between the two arms in perioperative complications, conversions, duration of surgery, or duration of postoperative stay, a significantly greater degree of LN assessment by the robotic technique was observed in regards to the median number of sampled LN stations (6, IQR 4-6 vs 4, IQR 3-5; p=0.0002), hilar LNs (7, IQR 5-10 vs 4, IQR 2-7; p=0.0003), and mediastinal LNs (7, IQR 5-10 vs 5, IQR 3-7; p=0.0001). Conclusions: The results of this trial demonstrated that RATS was not superior to VATS considering perioperative outcome for early-stage NSCLC but the robotic approach allowed an improvement of LN dissection. Further studies are suggested to validate the results of this trial. Clinical Trial Registry Number: NCT02804893 (clinicaltrials.gov).